The beginnings of Food Anthropology in Spain (1950-1975) - Tomé Martín, Pedro; Moro Gutiérrez, Lourdes; Lamarque, Muriel (Revista de Antropología Social, 2026)
Although it is difficult to speak of anthropology of food until the 1980s, some of the ethnographies carried out in Spain between 1950 and 1975 raised reflections on food uses and practices that can contribute to a better understanding of some of the current research in this field. This article focuses on some ethnographies that, because of their contributions, could be considered as forerunners for current Food Anthropology in Spain. It is not so much a scholarly exercise but an attempt to show how research carried out decades ago introduced some concepts and questions which, analysed with different methodologies, maintain their relevance. To this end, after some contextual references, this text focuses on the contributions made by José María Arguedas, Susan Tax Freeman, Ramón Valdés and Renate Lellep who, from different but convergent positions, payed special attention to questions related to food that arise in their ethnographies.
Keywords: anthropology of food; history of anthropology; rituals of commensality; hunger